2022
DOI: 10.3389/fmolb.2022.884839
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Microenvironment Heterogeneity-Based Score System Predicts Clinical Prognosis and Response to Immune Checkpoint Blockade in Multiple Colorectal Cancer Cohorts

Abstract: Despite immune checkpoint blockade (ICB) therapy contributed to significant advances in cancer therapy, only a small percentage of patients with colorectal cancer (CRC) respond to it. Identification of these patients will facilitate ICB application in CRC. In this study, we integrated multiple CRC cohorts (2,078 samples) to construct tumor microenvironment (TME) subtypes using TME indices calculated by CIBERSORT and ESTIMATE algorithms. Furthermore, a surrogate quantitative indicator, a tumor microenvironment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Wang et al applied five genes, including SERPINE1, to construct a tumor microenvironment immune gene (TMEIG) score system, which can accurately predict the prognosis and immune checkpoint blockade response of colorectal cancer patients. Meanwhile, SERPINE1 may be a potential target related to immunotherapy ( Wang et al, 2022 ). Smirnova et al suggested that SERPINE2 is required in the extracellular milieu of tumors where it acts in multiple ways to regulate tumor matrix deposition, thereby controlling tumor cell dissemination in breast cancer ( Smirnova et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al applied five genes, including SERPINE1, to construct a tumor microenvironment immune gene (TMEIG) score system, which can accurately predict the prognosis and immune checkpoint blockade response of colorectal cancer patients. Meanwhile, SERPINE1 may be a potential target related to immunotherapy ( Wang et al, 2022 ). Smirnova et al suggested that SERPINE2 is required in the extracellular milieu of tumors where it acts in multiple ways to regulate tumor matrix deposition, thereby controlling tumor cell dissemination in breast cancer ( Smirnova et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The “cytokine–cytokine receptor interaction” pathway was also remarkably concentrated in HOXC6 . However, the predictive capacity of the model and the relationship among the five genes have not been verified in patients with CRC [ 50 ]. Another study suggested that HOXC6 may affect the immune microenvironment and promote tumor evolution by adjusting the EMT signaling pathway in gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptome data of above five cohorts were the microarray data from GPL570 platform. The method of merging multiple data sets and the procedure of removing batch effects were carried out as reported in our previous study (Wang et al 2022a ).The transcriptome data (FPKM) and clinical information of the TCGA COAD cohort were downloaded from the UCSC website (Navarro Gonzalez et al 2021 ). Then FPKM was converted to transcripts per kilobase million (TPM) and further log-2 transformed in next analysis.…”
Section: Methodsmentioning
confidence: 99%